Drought characteristics and propagation under anthropogenic impacts: A regional-scale modelling analysis in four Large Basins of China - Haoran Hao; Ningpeng Dong; Mingxiang Yang; Xin Huang; Hejia Wang; Hao Wang (Journal of Hydrology: Regional Studies)
Study region: The Songhua River Basin, the Yellow River basin, the Yangtze River basin, and the Pearl River Basin in China. Study focus: Understanding the drought evolution under changing environment is crucial to sustainable water management, especially for China where there are increasing anthropogenic activities. We employ a national-scale land surface-hydrological model (CLHMS v1.1) with representations of human water management and enhance it with dynamic land use setting to investigate the impact of human activities on the drought regime. We first identify the meteorological droughts and hydrological droughts using Standardized Precipitation Index (SPI) and Standardized Streamflow Index (SSI), respectively. Then, two controlled simulation experiments, namely the human altered scenario and the natural scenario, are designed to analyze the human impact on the drought characterisics and propagation. New hydrological insights for the region: The model accurately simulates the SSI under human impacts, with a correlation coefficient ranging from 0.78 to 0.93. In northern basins, human activities decrease the number of hydrological drought events by 50 %, while increasing their severity, duration, and recovery time. Additionally, human activities have prolonged the average propagation time from meteorological to hydrological droughts by approximately 3.4 months. For southern basins, the impact of human activities on the drought regime is similar to that in northern basins but to a lesser extent.